2018 Conference on Design and Architectures for Signal and Image Processing (DASIP) 2018
DOI: 10.1109/dasip.2018.8597044
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Methods Making Use of Backup Copies for Fault-Tolerant Scheduling on Embedded Multiprocessor Systems

Abstract: As transistors scale down, systems are more vulnerable to faults. Their reliability consequently becomes the main concern, especially in safety-critical applications such as automotive sector, aeronautics or nuclear plants. Many methods have already been introduced to conceive fault-tolerant systems and therefore improve the reliability. Nevertheless, several of them are not suitable for real-time embedded systems since they incur significant overheads, other methods may be less intrusive but at the cost of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A primary/backup online scheduling approach has been proposed in [41] that guarantees the reliability of the hard real-time system without increasing overhead and the need for extra hardware components. In the primary/backup approach, two identical versions for each task are scheduled on two different cores in a way they do not have any execution overlap.…”
Section: A Standby-sparing (Ss) and Primary/backup (P/b)mentioning
confidence: 99%
See 1 more Smart Citation
“…A primary/backup online scheduling approach has been proposed in [41] that guarantees the reliability of the hard real-time system without increasing overhead and the need for extra hardware components. In the primary/backup approach, two identical versions for each task are scheduled on two different cores in a way they do not have any execution overlap.…”
Section: A Standby-sparing (Ss) and Primary/backup (P/b)mentioning
confidence: 99%
“…It has shown that FFSS reduces the computation complexity more than the exhaustive search. The scheduling approach in [41] with the FFSS policy achieves a significant improvement in the performance of periodic applications. However, the simulations do not consider real-world task sets and platforms.…”
Section: A Standby-sparing (Ss) and Primary/backup (P/b)mentioning
confidence: 99%